Does Project Management Affect Business Productivity? Evidence From Australian Small to Medium Enterprises. Issue 6 (18th November 2014) - Pollack, Julien; Adler, Daniel
ABSTRACT: A fundamental assumption of project management practice and research is that using project management to achieve organizational objectives improves organizational performance. However, there is little published research that directly questions this assumption. This paper tests the hypothesis that using project management increases the productivity of small to medium enterprises, using data from two longitudinal surveys of Australian businesses with less than 200 staff members. These data were used to create models of the relationship between productivity and business skills using binary logistic regression. The models demonstrate that project management has a significant impact on small to medium enterprise productivity.